Fostering Creative Mathematical Thinking with a Flipped Classroom Approach - Zakiyah, Zenzen; Karlimah, K; Hidayat, Syarip (Universitas Sarjanawiyata Tamansiswa, 2023)
Mathematics education in this digital era requires innovative and creative learning models to improve the quality and creativity of students. The flipped classroom model has become one of the alternatives that can be implemented in mathematics education in the 21st century. This study aims to review several articles examining the flipped classroom model on elementary school student's mathematical creative thinking skills. The research method used is a literature review which begins with identifying research problems, searching for literature, evaluating data, and analyzing it. The literature review results show that the flipped classroom model has several advantages over the conventional learning model, such as increasing student engagement in the learning process and providing opportunities for students to develop creative thinking skills. In addition, using the flipped classroom model also positively influences students' abilities to solve measurement-related problems. Flipped classroom model provides a learning experience that is fluency, flexibility, originality, and elaboration. This article offers several recommendations for the development of the flipped classroom model in the future, such as the use of more varied learning media and the development of more interactive teaching materials. Therefore, this article can be a reference for educators and researchers interested in developing effective learning models to enhance students' mathematical creative thinking skills.